Epidemiology of injuries in juniors participating in top-level karate competition: a prospective cohort study - Cierna, D.; Barrientos, M.; Agrasar, C.; Arriaza, R. (British Journal of Sports Medicine, 2018)
Background: Karate is a popular combat semi-contact sport among juniors, but there are only few studies available on the epidemiology of injuries in karate junior athletes.